In‐Hospital Mortality Rates in Older Patients with COVID‐19. Issue 10 (1st September 2020) - Mahiat, Cédric; de Terwangne, Christophe; Henrard, Séverine; Boland, Benoit
Abstract : See the Reply from Huang et al . See the Reply by Sun et al .